Economic violence robs women of financial rights in Saudi Arabia - Causes and treatment - Abu Rashed, Hitaf Jumah (Journal of Humanities & Social Sciences, 2022)
Violence is a serious problem, and it is a natural consequence of the social, moral and cultural level reached by human societies, which does not reflect humanity and human cognitive progress. Thus relations have deteriorated in all social institutions. In order to reach the manifestations of economic violence against women, the research followed the descriptive analytical approach to monitor economic violence against women, with the aim of clarifying the relationships between the different variables and phenomena. This research aims to reveal the most important causes of women's economic violence and its relationship to the economic system that governs society, as well as to reveal the credibility of laws and international agreements that call for changing the economic status of women. The research ended with a number of results, the most important of which is that one of the main manifestations of economic violence against women is the prevention of work, the deprivation of their salary and the prevention of their inheritance. The pace and diversity of change have accelerated significantly in recent years as the situation of Saudi women is different today than it was half a century ago. The research also recommended working on women's empowerment and making them aware of their financial and legal rights. As well as promoting the work of women and preserving their dignity at work without coercion, exploitation or discrimination for any reason.
Keywords: violence; economy; women